TOPIRAMATE FOR MIGRAINE PROPHYLAXIS AMONG CHILDREN AGED 5 TO 15 YEARS - Surani, Muhammad Khalil; Yousuf, Muhammad; Anjum, Naveed; Khan, Sabiha; Hasan, Gul; Hussain, Sajid (Journal of Ayub Medical College Abbottabad, 2021)
Background: Migraine is known to be a common neurological disorder among children. Newer anti-epileptic agents like topiramate (TPM) have shown to decrease the frequency of headache but not much work about safety and efficacy of TPM is seen in the paediatric population with migraine. This study was aimed to find out the efficacy and safety of TMP for migraine prophylaxis among children aged 5-15 years. Methods: A total of 132 children having migraine headache according to ICHD-II criterion for duration of at least 6 months, from 5-15 years of age were enrolled. Frequency of headache, severity of headache and duration of headache were compared before and after 3 months of TPM treatment. Side effects of TPM treatment were also observed. Results: In a total of 132 children, 80 (60.6%) were female and 52 (39.4%) males. Mean age was 9.52±2.5 years. Good response of TPM treatment was observed in 102 (77.3%) children. Significant decrease (p value <0.05) was noted in headache frequency, severity and duration following TPM treatment. No serious side effects of TPM treatment were noted. Conclusion: Topiramate is noted to be effective and safe for migraine prophylaxis among children. Reduction in headache frequency, severity as well as duration and disability scores are recorded after TPM treatment.